2015
DOI: 10.3389/fncel.2015.00408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitivity in the enteric nervous system

Abstract: The enteric nervous system (ENS) autonomously controls gut muscle activity. Mechanosensitive enteric neurons (MEN) initiate reflex activity by responding to mechanical deformation of the gastrointestinal wall. MEN throughout the gut primarily respond to compression or stretch rather than to shear force. Some MEN are multimodal as they respond to compression and stretch. Depending on the region up to 60% of the entire ENS population responds to mechanical stress. MEN fire action potentials after mechanical stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 46 publications
2
29
0
2
Order By: Relevance
“…Cx43 hemichannel might also be a conduit for release of metabolites and neurotransmitter precursors, such as lactate and glutamine, which can affect normal neuronal functioning (Giaume, Même, & Koulakoff, ). Furthermore, it is possible that here observed effects of gliotransmission are also regulated, at least in part, on the afferent side of gut local reflex loops—perhaps by communication between EG with enteroendocrine cells (Bohorquez et al, ) or mechanosensitive enteric neurons (Mazzuoli‐Weber & Schemann, ). These are all open issues that need to be experimentally addressed in future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cx43 hemichannel might also be a conduit for release of metabolites and neurotransmitter precursors, such as lactate and glutamine, which can affect normal neuronal functioning (Giaume, Même, & Koulakoff, ). Furthermore, it is possible that here observed effects of gliotransmission are also regulated, at least in part, on the afferent side of gut local reflex loops—perhaps by communication between EG with enteroendocrine cells (Bohorquez et al, ) or mechanosensitive enteric neurons (Mazzuoli‐Weber & Schemann, ). These are all open issues that need to be experimentally addressed in future.…”
Section: Discussionmentioning
confidence: 98%
“…or mechanosensitive enteric neurons(Mazzuoli-Weber & Schemann, 2015). These are all open issues that need to be experimentally addressed in future.ACKNOWLEDGMENT We thank Drs.…”
mentioning
confidence: 98%
“…Several studies have reported distinct mechanosensitive responses in enteric neurons to tensile stress (stretch), compressive stress (volume injection, glass probe, or von Frey hair), shear stress, and cell swelling (hypoosmotic solutions) (Dong, Jiang, Dong, & Mittal, 2014; Hibberd, Zagorodnyuk, Spencer, & Brookes, 2012; Kugler et al, 2015; Kunze et al, 1999; Kunze, Clerc, Furness, & Gola, 2000; Kunze et al, 1998; Mayer & Wood, 1975; Mazzuoli & Schemann, 2009, 2012; Spencer & Smith, 2004). While these studies suggest roles in mechanosen-sitivity sensing and control of muscle activity, as well as a servo-feedback loop (Mazzuoli-Weber & Schemann, 2015), the identities of the mechano-sensitive ion channels responsible for mechanotransduction are largely unknown. Only one study identified a molecular transduction mechanism, which involved the activation of a large conductance BK-like potassium channel (Kunze et al, 2000).…”
Section: Mechanosensitive Ion Channelsmentioning
confidence: 99%
“…This indicates that duodenal sensitivity to distension‐induced contraction in rabbits on long‐term low‐fiber diet decreased. It is well known that the gastrointestinal tract contains intrinsic and extrinsic enteric neurons, smooth muscle cells, and interstitial cells of Cajal (ICC), which respond to mechanical deformations by altering transmembrane ionic currents in a process called mechanoelectrical coupling . It has been demonstrated that factors such as aging and diabetes change the mechanosensitivity.…”
Section: Discussionmentioning
confidence: 99%